Automatic extraction of semantic colors in sports video - Wang, Lei; Zeng, Boyi; Lin, Steve; Xu, Guangyou; Shum, Harry (International Conference on Acoustics, Speech, and Signal Processing (ICASSP), 2004)
Color has been widely used in sports video analysis. Previous techniques, however require color models from prior information or user interaction, and do not address the problem of how to automatically form color models from a video in an arbitrary sports setting. In this paper, we propose an automatic technique for extracting color models of the playing surface and the team uniforms, which can be used in higher-level processes such as tracking and recognition. Unlike most previous methods, our approach is capable of handling multi-colored patterns like striped uniforms and playing fields. Multiple forms of color processing are used to analyze video frame content, which are then used iteratively to refine the color models. The results of our color modeling technique have been applied to shot classification, and experiments on videos of different sports have verified our approach.